Consolidation in Banking Sector Through Mergers and Acquisition - Sharma, S. K (Journal of Commerce and Trade, 2010)
Public sector banks hold over 75 percent of total assets of the banking industry, with the private and foreign banks holding 18.2 percent and 6.5percent respectively . Consolidation is an effective means to acquire competitive size , geographic expansion, huge loan portfolios ,improved technology ,product diversification and reduced transaction costs in Indian banking sector. . More over, bigger the size, better would be a bank’s capital adequacy ratio and risk management capabilities. So the size does matter. Banks in India need to be large to keep pace with the global aspiration of Indian corporates that are growing in size. This paper exhibits the objectives, needs and advantages of consolidation in banking sector in India. It also emphasis banks consolidation in Indian perspectives and motives of merger and acquisition in India.